Pembiasaan Tradisi Aswaja sebagai Upaya Pencegahan Radikalisme di Madrasah Aliyah Matholi’ul Huda Kedung Jepara - Fathur Rohman; Hanifa A'la (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2020)
This article discusses the traditional Aswaja practices that implemented in Madrasah Aliyah (MA) Matholi'ul Huda Kedung Jepara as a means of preventing radicalism. There are two issues that will be discussed in this article, namely the forms of the Aswaja tradition that took place in MA Matholi'ul Huda Kedung Jepara and the habituation of the Aswaja tradition within the MA Matholi'ul Huda Jepara. This study was conducted using a qualitative approach with a case study method. The data in this study were collected using participatory observation techniques, interviews, and documentation. The data were then analyzed descriptively qualitatively through three stages, namely presentation, reduction and verification. From the results of this analysis, it is known that the traditions that are accustomed to in MA Matholi'ul Huda Kedung Jepara are khatmil quran, tahlilan, istigtsah, pilgrimage to the grave, and tawassul. Khatmil Qur'an and Tahlilan habituated once a week. While Istighatsah, grave pilgrimage, and tawassul are carried out at the beginning of the school year, before the semester exams, and the National Examination. This traditional habituation is a form of learning so that students have a caring attitude towards tradition and respect for the scholars who have started the tradition. This attitude of caring and respect will in turn be both an antidote and an antidote to the